STUDY AND DESIGN OF SINGLE PHASE CONVERTER USING OF SINGLE PHASE TRANSFORMER - Kumrey, G.R.; Mahobia, S. K. (International Journal of Research -GRANTHAALAYAH, 2016)
The field of electrical transformer are most important equipment which is use to convert ac voltage or current like lower to higher , higher to lower without change in the frequency . its primary side and secondary side are isolate from each other and it can higher or lower voltage level the apparent value of electrical passive element like inductive , resistive . It use to transfer electrical energy for long distance with higher voltage level .the electrical power transmission,distribution through transformer for factories and home . AC supply can easily generated by a convenient voltage and transformed into much higher voltage for transmission and distribution purpose.